Digital techniques for wideband receivers - Tsui, James, 1935-; Cheng, Chi-Hao (Coleção Radar., 2015)
The book has 18 chapters that cover the following topics: requirements and characteristics of electronic warfare receivers; Fourier transform and related operations; analog-digital converters, amplifiers, and their interface; frequency downconverters; sensitivity and detection problems; phase measurement and zero crossing; monobit receivers; frequency chanelization and processing; high-resolution spectrum estimation; detection of frequency modulated signals; concept of analog-to-information; angle of arrival measurements; time reversal study; multiple fast Fourier transform electronic warfare receiver; and receiver testing.